The Experiences of Parents and Infants Using a Home-Based Art Intervention Aimed at Improving Wellbeing and Connectedness in Their Relationship - Armstrong, Victoria Gray; Ross, Josephine (Frontiers in Psychology, 2022)
During the period of Covid 19 restrictions, we offered vulnerable families with 0- to 3-year-old children boxes of art resources and guided creative activities to do together at home. This paper explores families’ experiences of this intervention, highlighting their perceptions of change in wellbeing and attachment. There is a developing case for the social benefits of art, including the impact of arts on mental health and on the wellbeing of children. However, we know that social factors impact upon arts participation, and existing inequalities and mental health difficulties have been exacerbated in the context of the pandemic. This project aimed to adapt to restrictions, to provide a meaningful remote intervention, supporting parent-infant dyads to have positive interactions through art making. We sought to explore the benefits of this intervention for infants and parents with a view to understanding more about the psychological benefits of art participation and about ways to engage families into art making, as well as thinking about how best we can evidence these kinds of arts in health interventions. Preliminary findings showed promising outcomes from the art boxes (Armstrong and Ross 2021) and this paper brings together the full results, primarily based on interviews with 16 parents and 4 referrers alongside collected feedback. We highlight potential mechanisms for change within the intervention and detail the perceived impact of the art boxes in supporting attachment. Parents felt that the art-boxes facilitated changes in their own wellbeing that would make them more available to connection, and recognised changes for babies that reflected their increased capacity to mentalise about their child. Importantly, there were also concrete changes for the dyad that represented improved connection, such as more playful time together and increased shared attention and eye contact. Our observations suggest that the quality of the parent-infant relationship benefited from home-based art intervention, and we speculate about the potential efficacy of this approach beyond the pandemic.